Incorporating the Roles of Feature Size and Build Orientation in the Process-Structure-Property Relationship for Additively Manufactured Parts - Chinmay Phutela; Federico Bosio; Alya Alhammadi; Nujood Alshehhi; Lewis Kindleyside; Nesma T. Aboulkhair (Metals, 2023)
Laser powder bed fusion (L-PBF) additive manufacturing has reached wide-scale technology readiness for various sectors. However, some challenges posed by the complex nature of the process persist. Limited studies investigated the correlation between the micro- and macroscopic properties of L-PBF AlSi10Mg parts and the features’ sizes with the build orientation in mind. Therefore, this study presents a comprehensive view on the “size effect” for samples larger than those available in the literature (up to 12 mm) on the defects, microstructure evolution, and mechanical properties in two build orientations using a fixed set of process parameters. Microstructural differences were observed between the build orientations, but no considerable difference with size change was detected. The porosity content was inversely proportional to the feature size irrespective of the build orientation, leading to an increase in ductility that was more evident in the horizontal specimens (~44%). This was attributed to an in-situ heat treatment. Although specimens oriented parallel to the build direction showed no significant size-effect in terms of the mechanical properties (hardness and tensile), anisotropy was evident. Based on the findings presented in the study and the scientific explanations discussed corroborated by thermal imaging during processing, it is concluded that although any set of ‘optimised’ process parameters will only be valid for a specific size range, the severity of the size-effect changes dynamically based on the range.